On the existence of solution of a two-point boundary value problem in a cylindrical floating zone - Shi Yongdong; Du Liangsheng (International Journal of Mathematics and Mathematical Sciences)
Existence of one solution for a two-point boundary value problem with a positive parameter Q arising in the study of surface-tension-induced flows of a liquid metal or semiconductor is studied. On the basis of the upper-lower solution method and Schauder's fixed point theorem, it is proved that the problem admits a solution when 0≤Q≤12.683. This improves a recent result where 0≤Q<1.